The Influence of Environmental Knowledge, Social Media Influence, and Green Marketing Communication on Green Consumer Behavior of Consumers of Sustainable Fashion Products - Sulistyo Budi Utomo; Anton Nurcahyo; Iwan Henri Kusnadi; Yusnindar Yusnindar; Rezky Nurbakti (Indonesian Journal of Innovation Multidisipliner Research, 2026)
The purpose of this research is to analyze the effect of Environmental Knowledge, Social Media Influence and Green Marketing Communication toward Green Consumer Behavior on consumers of sustainable fashion products. The study adopted a quantitative design and survey method with 220 respondents who had purchased sustainable fashion products, selected through purposive sampling technique. Data collection was by online questionnaire and data analysis was by multiple linear regression. The results show that Environmental Knowledge, Social Media Influence and Green Marketing Communication have a positive and significant effect on Green Consumer Behavior both partially and simultaneously. The research result shows that the higher environmental knowledge, social media positive influence and green marketing communication can improve the environmentally friendly consumption behavior. It makes theoretical contributions to the green marketing and consumer behavior literature, and provides practical implications for sustainable fashion companies in developing marketing strategies for sustainability.